An analysis of anatomy education before and during Covid‐19: August–December 2020. Issue 1 (20th January 2022) - Attardi, Stefanie M.; Harmon, Derek J.; Barremkala, Malli; Bentley, Danielle C.; Brown, Kirsten M.; Dennis, Jennifer F.; Goldman, Haviva M.; Harrell, Kelly M.; Klein, Barbie A.; Ramnanan, Christopher J.; Farkas, Gary J.
Abstract: Coronavirus disease‐2019 (Covid‐19) disrupted the in‐person teaching format of anatomy. To study changes in gross anatomy education that occurred during August–December, 2020 compared to before the pandemic, an online survey was distributed to anatomy educators. The 191 responses received were analyzed in total and by academic program, geographic region, and institution type. Cadaver use decreased overall (before: 74.1 ± 34.1%, during: 50.3 ± 43.0%, P < 0.0001), as well as across allopathic and osteopathic medicine, therapy, undergraduate, and veterinary programs ( P < 0.05), but remained unchanged for other programs ( P > 0.05). Cadaver use decreased internationally and in the US ( P < 0.0001), at public and private ( P < 0.0001) institutions, and among allopathic medical programs in Northeastern, Central, and Southern ( P < 0.05), but not Western, US geographical regions. Laboratories during Covid‐19 were delivered through synchronous (59%), asynchronous (4%), or mixed (37%) formats ( P < 0.0001) and utilized digital resources (47%), dissection (32%), and/or prosection (21%) ( P < 0.0001). The practical laboratory examination persisted during Covid‐19 ( P = 0.419); however, the setting and materials shifted to computer‐based ( P < 0.0001) and image‐based ( P < 0.0001), respectively. In‐person lecture decreased during Covid‐19 (before: 88%, during: 24%, P = 0.003). When anatomy digital resources were categorized, dissection media, interactive software, and open‐access content increased ( P ≤ 0.008), with specific increases in BlueLink, Acland's Videos, and Complete Anatomy ( P < 0.05). This study provided evidence of how gross anatomy educators continued to adapt their courses past the early stages of the pandemic.